Keselamatan dan Proteksi Baterai Sepeda Motor Listrik: Studi Kasus Analisis Kegagalan Pada Insiden Kebakaran Kapal Motor Penumpang (KMP) Tranship 1 - Khrisna, R. Hanggoro Ananta; Yanto; Soewono, Arka Dwinanda (Cylinder : Jurnal Ilmiah Teknik Mesin, 2025)
The adoption of electric motorcycles in Indonesia has seen rapid growth, driven by the push toward a sustainable energy transition. However, battery safety remains a significant concern, particularly with Lithium-ion and Sealed Lead Acid (SLA) battery types. This study aims to analyze the failure mechanisms behind a fire incident on the passenger motor vessel (KMP) Tranship 1, which was allegedly triggered by a Lithium-ion battery from an electric motorcycle lacking an adequate protection system. The analysis employs Fishbone Diagrams and Fault Tree Analysis (FTA), drawing on data from field case studies, evaluations of protection systems in locally manufactured electric motorcycles, and a review of relevant technical literature. The root cause analysis using the Fishbone Diagram identifies several contributing factors to fire risk, including improper usage and charging practices, inadequate transportation methods, extreme environmental conditions, and equipment failure. Findings from the Fault Tree Analysis highlight the critical role of safety components such as fuses, circuit breakers, and ventilation systems in preventing battery-related fires or explosions in electric vehicles. Based on these findings, the study recommends the implementation of multilayered protection systems, the use of standardized chargers, and the development of national regulations aligned with international safety standards. The incorporation of a Battery Management System (BMS) is also strongly recommended to enhance battery safety and reliability.